2016
DOI: 10.1080/19932820.2017.1260886
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music therapy under general anesthesia in patients undergoing abdominal surgery

Abstract: Background: Music therapy, an innovative approach that has proven effectiveness in many medical conditions, seems beneficial also in managing surgical patients. The aim of this study is to evaluate its effects, under general anesthesia, on perioperative patient satisfaction, stress, pain, and awareness. Methods: This is a prospective, randomized, double-blind study conducted in the operating theatre of visceral surgery at Sahloul Teaching Hospital over a period of 4 months. Patients aged more than 18 undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 26 publications
5
47
1
9
Order By: Relevance
“…Studies in the literature detected positive effects of music on anxiety and vital signs (17,20,23). It has been shown that listening to relaxing, calming music positively affects the pulse rate in the studies mentioned in the literature (1,10,13,17,20,(23)(24)(25). In our study, it has been found that the pre-operative heart rate of the experimental group was higher than the control group.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Studies in the literature detected positive effects of music on anxiety and vital signs (17,20,23). It has been shown that listening to relaxing, calming music positively affects the pulse rate in the studies mentioned in the literature (1,10,13,17,20,(23)(24)(25). In our study, it has been found that the pre-operative heart rate of the experimental group was higher than the control group.…”
Section: Discussionsupporting
confidence: 57%
“…According to the result of the research, music has no effect on the patients' fever rate. In the studies performed, it was stated that the experimental group's diastolic and systolic blood pressure was lower than the control group (1,10,20,21,(24)(25)(26). However, Sabzevari et al (23) found that the systolic blood pressure was lower in the group in which the music was listened to, but the diastolic blood pressure was not different.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Music medicine as a non-pharmacologic intervention has demonstrated benefits in awake surgical procedures concerning anxiety and blood pressure [14]. Patients under general anesthesia also benefited from improved pain scores and patient satisfaction [15]. Music therapy can be a cost-effective and low-risk intervention to decrease the stress response to surgery and improve patient experience and satisfaction during total knee arthroplasty [16].…”
Section: Discussionmentioning
confidence: 99%
“…The use of music as a healing tool dates back thousands of years. 38 The method relies on the relaxing properties of music to help repair, maintain, and improve the physiology and psychology of the individual's mind. Conrad et al conducted a randomized study to identify the mechanisms of music-induced relaxation and found that a musical intervention caused an increase in the concentration of plasma growth hormone and a decrease in interleukin-6 and epinephrine.…”
Section: Music Therapymentioning
confidence: 99%